Improvements on sintering and thermal expansion of lithium aluminum silicate glass-ceramics. Issue 11 (1st August 2020) - Soares, Viviane Oliveira; Rodrigues, Alisson Mendes
Abstract: Glass-ceramics (GCs) are inorganic, non-metallic materials prepared by controlled crystallization of glasses, which contain at least one functional crystalline phase and a residual glass. In this work, to find the best compromise between coefficient of thermal expansion (CTE) and high sinterability on the LAS GCs, we accomplish changes in the minority oxides (MgO, ZnO, B2 O3, P2 O5, K2 O, and SnO2 ) of a LAS glass composition (Li2 O–Al2 O3 –SiO2 ). All LAS GCs were sintered non-isothermally. We propose the use of glass stability parameters ( K A, K H, and K M ) to point out the most promising glass composition concerning sintering. Indeed, the glass compositions which presented a low tendency to crystallization during the heating, resulted in GCs with the lowest porosities. The porosity analysis was performed through image analysis of optical micrographs. The compositional changes in the most sinterable glasses consisted of MgO reduction (from 1.64 to 0.85 mol%), increases in B2 O3 (from 1.4 to 1.9 mol%), and keeping the sum of ZnO and K2 O between 1.7 to 1.8 mol%. The changes in minority oxides of the parent glass composition significantly modified the CTE values of the LAS GCs, mainly due to changes in GC crystallinity. The changes in the glass composition allowed to obtain a highly dense sintered GC (0.4 ± 0.1% in porosity), having an appropriated CTE (0.34 × 10 −6 K -1 ) to applications as induction cooktop plates.